Art Fundamentals: Theory and Practice - Ocvirk, Ottog G.; Ocvirk, Otto G. (Boston, Mass. : McGraw-Hill, 2002)
"ART Fundamentals: Theory and Practice" (ninth edition) by Otto G. is a comprehensive textbook that introduces the essential elements and principles of visual art. The book serves as a foundational resource for students and enthusiasts in the field of art, providing a well-rounded understanding of artistic concepts, techniques, and historical contexts.
Includes bibliographical references (p. 343-344) and index.
Keywords: Art -- Technique; Art Education -- Creativity; Visual Arts -- Design Principles